Farber Disease Mimicking Juvenile Idiopathic Arthritis: The First Reported Case in Qatar and Review of the Literature. (10th February 2022) - Al-Naimi, Amal; Toma, Haneen; Hamad, Sara G.; Ben Omran, Tawfeg
Abstract : Farber disease (FD) is an extremely rare autosomal recessive disorder caused by the deficiency of lysosomal acid ceramidase. It is characterized by a triad of progressive multiple joints' involvement, subcutaneous nodules, and hoarseness of voice. In this report, we describe a 23-month-old boy diagnosed with Farber disease. Initially, he was misdiagnosed as juvenile idiopathic arthritis (JIA) because he presented with joint swelling. However, the associated hoarseness of voice, subcutaneous nodules, and poor response to treatment all have questioned the diagnosis of JIA and prompted the suspicion of Farber disease as an alternative diagnosis. The diagnosis was later confirmed genetically by the presence of a homozygous pathogenic variant (p.Gly213Glu; c.638G > A in exon 8) in the ASAH1 gene. The present case illustrates the diagnostic journey of a child with Farber disease as well as highlights that FD should be considered in the differential diagnosis of early onset arthritis in the presence of subcutaneous nodules and/or hoarseness of voice.